2015
DOI: 10.1002/cjce.22235
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the yielding behaviour of oil sand slurries under vane and slump tests

Abstract: Yield stress measurements were carried out on slurries prepared from five different ore samples of varying contents of bitumen and fines in the sand fraction. The rheological measurements were performed using the vane, slump, and relaxation methods, as well as by extrapolation of equilibrium flow curves to zero shear rate. In the case of the vane tests, it was found that the yield stress values agreed better with the results obtained from the other techniques when the yield stresses were calculated using a tor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…Bitumen on the solids fraction of oil sands slurries has been shown to enhance aggregation of the solids in the suspension, based on a comparison of vane torque measurements in raw and toluene‐washed samples. [ 23 ] Overall, the conclusion of that paper was that bitumen on the surface of solids increased the aggregation behaviour of the suspension. Another study showed that bitumen in a quartz suspension must be present on the surface of quartz particles to cause aggregation; otherwise, it makes a negligible contribution to the aggregation of the particles.…”
Section: Resultsmentioning
confidence: 95%
“…Bitumen on the solids fraction of oil sands slurries has been shown to enhance aggregation of the solids in the suspension, based on a comparison of vane torque measurements in raw and toluene‐washed samples. [ 23 ] Overall, the conclusion of that paper was that bitumen on the surface of solids increased the aggregation behaviour of the suspension. Another study showed that bitumen in a quartz suspension must be present on the surface of quartz particles to cause aggregation; otherwise, it makes a negligible contribution to the aggregation of the particles.…”
Section: Resultsmentioning
confidence: 95%
“…With the change in the mixed liquid velocity, the pipe flow of the liquid–solid mixture presents the following flow patterns: a homogeneous flow, a heterogeneous flow, a heterogeneous flow with a sliding bed at the bottom, and a heterogeneous flow with a fixed bed at the bottom. It has been found that when the liquid–solid flow is homogeneous, there are two types of constitutive models for Newtonian and non-Newtonian fluids under different solid volume fractions. …”
Section: Introductionmentioning
confidence: 99%
“…Due to the rapidly increasing demand for energy and continuous depletion of conventional oil production, oil sands deposits have been extensively exploited as an unconventional petroleum resource. Steam-assisted gravity drainage (SAGD) is an effective technology for recovering heavy crude oil (denoted as bitumen) from deep oil sands deposits. , With the aid of a pair of horizontally parallel wells, a typical SAGD system consists of three processes: (i) steam is continuously injected into the upper well to heat adjacent bitumen reservoir; (ii) the mobilized bitumen flows into the lower well driven by gravity and is subsequently pumped up to the plant. It is noteworthy that a considerable amount of condensed water is produced along with the heated bitumen during the heat-exchange process, forming complex water-in-oil-in-water (W/O/W) emulsions, which is also denoted as SAGD emulsions.…”
Section: Introductionmentioning
confidence: 99%